Analisis Faktor Dan Dampak Perilaku Hiperaktif Siswa Sekolah Dasar Kelas Rendah Terhadap Hasil Belajar - Azi Miftah Rizqi; Belva Saskia Permana; Haldini Reygita; Deti Rostika; Ranu Sudarmansyah (Pusat Riset dan Inovasi Nasional, 2024)
The hyperactive behavior of students poses a serious challenge in the school learning process. This article employs a literature review method to identify the factors causing hyperactive behavior in elementary school students, particularly in lower grades, and analyze its impact on learning outcomes. Hyperactive disorder in children has been recognized in the medical field since the early 20th century, characterized by an inability to stay still, lack of self-control, and heightened activity levels. Factors contributing to hyperactive behavior stem from various aspects, including psychological factors, overindulgence, lack of discipline, pleasure orientation, sensor nerve weaknesses, genetic factors, prenatal factors, and environmental factors. The impact of hyperactive behavior on students hinders the learning process, diminishes focus and concentration, and affects the understanding of materials. Students exhibiting hyperactive behavior may encounter difficulties in socializing, family conflicts, and serious social issues, influencing their social-emotional development and learning environment, creating disruptions in the classroom and affecting classmates. Quality education should be able to accommodate the needs of students with hyperactive behavior to ensure optimal social, emotional, and academic development for each child.